"An Investigation on the Histologic Responses of Periapical Tissues Following Retrofilling with Root MTA and Portland Cement Type I Versus Pro Root MTA in the Canine Teeth of Cats " - M. Zarabian; H. Razmi; MR. Sharifian; D. Sharifi; F. Sasani; A. Mousavi (Tehran University of Medical Sciences, 2004)
Statement of the Problem: Endodontic surgery if required is considered as an additive therapy after classic endodontic treatments. The most prevalent type of endodontic surgeries are apicoectomy and corrective surgeries. Type of material applied in apicoectomies is of high importance. Root end filling material should not only be biocompatible but also provide appropriate seal. Considering these findings, the subject of this paper was to compare the histologic responses of the periradicular tissues after using Root MTA and Portland cement, as Root end fillings, with Pro Root MTA. Purpose: The aim of the present study was to introduce a suitable material for root end filling. Materials and Methods: The canals of sixty maxillary canines of cats, after cutting the crowns and exposing the pulps, were instrumented 1 mm beyond the apex until 25 # file to develop periapical lesion after 28 days. They were then randomly divided into five groups. After apicoectomy, Pro Root MTA, Root MTA and Portland cement were placed, as root end filling materials in three experimental groups whereas the two remaining groups were considered as positive and negative controls. After 3, 6 and 12 weeks the animals were sacrificed and the specimens were stained for histologic evaluation under light microscope. The data were submitted to statistical analyses (Fisher exact test, k2 test and one- way variance analysis). Results: No statistically significant difference was found between these three materials in cementum apposition on roots and implanted materials, fibrous capsule formation and the severity of inflammation, however, bone formation in Root MTA group was significantly less than pro Root MTA and Portland cement groups. The extent of inflammation thickness in Portland cement group was significantly less than Pro Root MTA group. Conclusion: According to these findings if long term investigations with larger sample size confirm the obtained results of the present study, Root MTA and Portland cement which are cost- effective and readily available, can replace Pro Root MTA in endodontic surgeries.